195 The Application of Radiomics in Laryngeal Cancer: The Forgotten Cohort. (12th October 2021) - Rajgor, A; McQueen, A; Ali, T; Aboagye, E; Obara, B; Bacardit, J; McCuloch, D; Hamilton, D
Abstract: Background: Radiomics is a novel method of extracting data from medical images that is difficult to visualise through the naked eye. This technique transforms digital images that hold information on pathology into high-dimensional-data for analysis. Radiomics has the potential to enhance laryngeal cancer care and to date, has shown promise in various other specialties. Aim: The aim of this review is to summarise the applications of this technique to laryngeal cancer and potential future benefits. Method: A comprehensive systematic review-informed search of the MEDLINE and EMBASE online databases was undertaken. Keywords 'laryngeal cancer' OR 'larynx' OR 'larynx cancer' OR 'head and neck cancer' were combined with 'radiomic' OR 'signature' OR 'machine learning' OR 'artificial intelligence'. Additional articles were obtained from bibliographies using the 'snowball method'. Results: Seventeen articles were identified that evaluated the role of radiomics in laryngeal cancer. Two studies affirmed the value of radiomics in improving the accuracy of staging, whilst fifteen studies highlighted the potential prognostic value of radiomics in laryngeal cancer. Twelve (of thirteen) studies incorporated an array of different head and neck cancers in the analysis and only one study assessed laryngeal cancer exclusively. Conclusions: Literature to date has various limitations including, small and heterogeneous cohorts incorporating patients with head and neck cancers of distinct anatomical subsites and stages. The lack of uniform data on solely laryngeal cancer and radiomics means drawing conclusions is difficult, although these studies have affirmed its value. Further large prospective studies exclusively in laryngeal cancer are required to unlock its true potential.